Students’ Attitude Towards Creating Musical Content in Primary School - Marinšek, Miha; Hmelak , Maja (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Engaging in creativity in music offers the potential for enriching educational practices, with students taking an active role and experiencing music through practical activities. Creating one's own musical content fosters a lasting interest in music among students, where positive musical experiences play a crucial role in developing a positive attitude towards music education and a favourable perception of music even in adulthood. The fundamental purpose of the research was to examine the attitude of students (N = 104) towards creating musical content in the subject of Music Art in Slovenian primary school. The results indicate that activities connected with creating musical content are relatively popular among students, with improvisation and composing their own songs being the most favoured. Students perceive creating musical content as an enjoyable activity that makes them feel relaxed.